2020
DOI: 10.46496/medula.v7i1.11488
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kebiasaan Merokok dan Kondisi Lingkungan dengan Kejadian Tuberkulosis Paru di Wilayah Kerja Puskesmas Guali Tahun 2016 (The Relationship Between Smoking Habits and Environmental Conditions with The Incidence of Pulmonary Tuberculosis in the Work Area of Guali Public Health Center in 2016

Abstract: Background: Tuberculosis is an infectious disease caused by Microbacterium Tuberculosis, bacteria aerobic rods and acid resistance can be a pathogenic organism or pathogen microbacterium saprofit there are several, but only bovine and human strains are pathogenic to humans. Purpose: The purpose of the study was to examine the relationship between smoking habit and environmental conditions with the incidence of pulmonary tuberculosis in the work area of Guali public health Center in 2016. Method: The design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
3
0
0
1
Order By: Relevance
“…Subject with more male sex than women, It can be caused by several factors such as smoking habits, comorbidities disease and social factors where the average man has more activities outside the home than women (Azwar et al, 2017). This is in line with research conducted by Saida and Syamsiar (2020) with the results of the study showing a relationship between smoking and environmental conditions with the risk of being infected with tuberculosis due to smoking activities can damage the defense mechanisms of the lungs. (Saida & Syamsiar, 2020).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Subject with more male sex than women, It can be caused by several factors such as smoking habits, comorbidities disease and social factors where the average man has more activities outside the home than women (Azwar et al, 2017). This is in line with research conducted by Saida and Syamsiar (2020) with the results of the study showing a relationship between smoking and environmental conditions with the risk of being infected with tuberculosis due to smoking activities can damage the defense mechanisms of the lungs. (Saida & Syamsiar, 2020).…”
Section: Resultssupporting
confidence: 92%
“…This is in line with research conducted by Saida and Syamsiar (2020) with the results of the study showing a relationship between smoking and environmental conditions with the risk of being infected with tuberculosis due to smoking activities can damage the defense mechanisms of the lungs. (Saida & Syamsiar, 2020).…”
Section: Resultssupporting
confidence: 92%
“…This is a preventive measure that sufferers can take to limit the spread of the virus to others. This is also in line with research conducted by (Saputri et al, 2020), that wearing a mask when leaving the house can be an effort to prevent TB transmission. c. Cleaning well when coming home from outside in the home environment Participants revealed that the changes that occurred after they were diagnosed with Tuberculosis were by maintaining personal hygiene.…”
Section: Theme 1: Knowledge Of Preventivesupporting
confidence: 89%
“…Penelitian ini sejalan dengan Saida dan Syamsiar (2016) di Wilayah Kerja Puskesmas Guali menyatakan ada hubungan antara kebiasaan merokok dengan kejadian Tuberkulosis Paru BTA (+) di wilayah Kerja Puskesmas Guali tahun 2016 (19). Selain itu juga sejalan dengan penelitian Wahid (2017) di Puskesmas Rawat Inap Panjang menyatakan bahwa terdapat hubungan perilaku merokok dengan kejadian TB paru (20).…”
Section: Hubungan Kebiasaan Merokok Dengan Kejadian Tb Paruunclassified